The Influence Of Product Quality And Price On The Purchase Decision At Kedai Coffe "Abraham And Smith" Bandung (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Improved product quality and prices are basically aimed at the interests of companies, consumers. While the purpose of improving product quality is done by the company so that consumers are satisfied, thus increasing sales. For consumers, improving product quality is so that consumers can feel good quality so that consumers meet their needs and desires. And the purpose of the appropriate pricing is so that the company gets a profit that is in accordance with what is given, the price aims so that consumers can get their needs at prices that match what they want. This study aims to determine and analyze the effect of product quality and price on the purchasing decision. This analysis uses independent variables, namely product quality and price, and the dependent variable is the purchasing decision. Samples are carried out using the Slovin formula. Data collection was conducted with questionnaires distributed to consumers as many as 88 people. The magnitude of the influence of product quality and price on the purchasing decision is 70.38%. So the suggestion that product quality and price have a significant effect on the purchasing decision so that the company must be able to pay attention to the two variables.